(untitled) (Web of Teachers: Inderscience Research, 2025)
This study explores the metaphysical elements in Ted Hughes’ poetry, highlighting how his works reflect deep existential themes. Hughes, known for his powerful imagery and nature-centric poetry, frequently bridges the physical and spiritual worlds. His poems, such as The Thought-Fox, Thrushes, and Pike, incorporate themes of inspiration, survival, violence, and death, resonating with the traditions of metaphysical poetry. While Hughes is not classified as a metaphysical poet in the traditional sense, his works exhibit intellectual depth, symbolic richness, and philosophical exploration, aligning him with the metaphysical tradition.